CytoSorb® hemoadsorption and mechanical circulatory support in a newborn with refractory shock after congenital heart surgery. Issue 9 (September 2019) - Perez, Marie-Hélène; Maitre, Guillaume; Longchamp, David; Amiet, Vivianne; Natterer, Julia; Ferry, Thomas; Schneider, Antoine; Plaza Wuthrich, Sonia; Di Bernardo, Stefano
Refractory cardiogenic and vasoplegic shock after congenital heart surgery is a threatening condition leading to high morbidity and mortality. Control of hemodynamic and inflammatory response is fundamental in medical strategy. We report the case of a newborn with cardiogenic and vasoplegic shock secondary to cardiopulmonary bypass for atrioseptostomy and prostaglandin treatment in the context of hypoplastic left heart syndrome, successfully treated with a combination of mechanical circulatory support and cytokine hemoadsorption column (CytoSorb ® ). Vasopressor support was weaned during the time of treatment without multiple organ failure occurrence. The use of CytoSorb ® cartridge inserted in an extra-corporeal circuit even in a newborn is easy and feasible, as long as some precautions are considered. Routine monitoring of drugs levels is mandatory during the use of the cartridge and immediately after.